Evidence for genetic association between chromosome 1q loci and predisposition to colorectal neoplasia - Schubert, Stephanie A; Ruano, Dina; Elsayed, Fadwa A; Boot, Arnoud; Crobach, Stijn; Sarasqueta, Arantza Farina; Wolffenbuttel, Bruce; van der Klauw, Melanie M; Oosting, Jan; Tops, Carli M; van Eijk, Ronald; Vasen, Hans Fa; et al. (British journal of cancer, 2017)
BACKGROUND: A substantial fraction of familial colorectal cancer (CRC) and polyposis heritability remains unexplained. This study aimed to identify predisposing loci in patients with these disorders. METHODS: Homozygosity mapping was performed using 222 563 SNPs in 302 index patients with various colorectal neoplasms and 3367 controls. Linkage analysis, exome and whole-genome sequencing were performed in a family affected by microsatellite stable CRCs. Candidate variants were genotyped in 10 554 cases and 21 480 controls. Gene expression was assessed at the mRNA and protein level. RESULTS: Homozygosity mapping revealed a disease-associated region at 1q32.3 which was part of the linkage region 1q32.2-42.2 identified in the CRC family. This includes a region previously associated with risk of CRC. Sequencing identified the p.Asp1432Glu variant in the MIA3 gene (known as TANGO1 or TANGO) and 472 additional rare, shared variants within the linkage region. In both cases and controls the population frequency was 0.02% for this MIA3 variant. The MIA3 mutant allele showed predominant mRNA expression in normal, cancer and precancerous tissues. Furthermore, immunohistochemistry revealed increased expression of MIA3 in adenomatous tissues. CONCLUSIONS: Taken together, our two independent strategies associate genetic variations in chromosome 1q loci and predisposition to familial CRC and polyps, which warrants further investigation.
Keywords: nádorové proteiny; RNA, Messenger; Chromosome Mapping; kolorektální nádory; homozygot; Genetic Predisposition to Disease; Genotype; Chromosomes, Human, Pair 1; mikrosatelitní repetice; proteiny aktivující GTPasu; jednonukleotidový polymorfismus; Homozygote; Precancerous Conditions; prekancerózy; Adenomatous Polyposis Coli; Genetic Linkage; Microsatellite Repeats; lidské chromozomy, pár 1; Aryl Hydrocarbon Receptor Nuclear Translocator; GTPase-Activating Proteins; Polymorphism, Single Nucleotide; lidé; receptory aromatických uhlovodíků - jaderný translokátor; genetická vazba; mapování chromozomů; Humans; Neoplasm Proteins; Colorectal Neoplasms; genotyp; familiární adenomatózní polypóza; messenger RNA; genetická predispozice k nemoci